Methisoprinol for children with early phase dengue infection: a pilot study - Ompico, Melissa G. (Paediatrica Indonesiana, 2013)
Background Dengue fever is associated with many health complications and medical costs. Furthermore, there is currently no approved dengue antiviral medication or vaccine. Empiric evidence has suggested that patients who received supplemental methisoprinol therapy had faster recovery times and fewer complications . Objective To detennine the effects of oral methisoprinol on the clinical course and laboratory findings of children with early phase dengue infection. Methods We conducted a randomized, double-blind study from June to September 2012 on 22 children aged 2.7-16.8 years with laboratory-confirmed early dengue infection. Subjects had not previously received antithrombotic agents, nor did they have bleeding disorders or immunodeficiency. We randomized the subjects to receive either oral methisoprinol (100 mg/kg BW/day, divided into four doses) or placebo for 72 hours, with 11 subjects per group. The primary endpoint was fever clearance time (FCT), and secondary endpoints were platelet nadii; white blood cell (WBC) nadii; maximum hemoconcentration, length of hospital stay, and development of complications . Results The mean decrease in WBC count was less with methisoprinol than with placebo [1.14 (SD 0.84) vs 2.60 (SD 3.12) x [09 /L; P = 0.004]. In addition, the mean decrease in platelet count was less in patients on methisoprinol [38.36 (SD 58.3) vs. 50.46 (SD 73.42) x 109/L; P=0.046]. No significant differences between the two groups were found for FCT (P=0.158), length ofhospital stay (P=0.511), hemoconcentration, or dengue complications. Conclusion Methisoprinol initiated at an early phase in dengue infection reduced the anticipated leukopenia by 56% and thrombocytopenia by 24%. Hence it can be used along with standard approved fluid and antipyretic therapy.